Efficacy and Safety of Misoprostol for Prevention of Post-Partum Haemorrhage: A Comparative Study (Journal of National Institute of Neurosciences Bangladesh, 2022)
Background: Post-partum haemorrhage condition is a serious condition after delivery.Objective: The purpose of the present study was to see the efficacy and safety of misoprostol for the prevention of post-partum haemorrhage.Methodology: This analytic cross-sectional study was carried out in the Department of Gynaecology and Obstetrics at Mymensingh Medical College Hospital (MMCH), Mymensingh, Bangladesh from January 2006 to June 2006 for a period of six months. Pregnant women who were admitted in MMCH during the above period and were expected to have vaginal delivery and women at term with singleton pregnancy were included as study population. Women were divided into 2 groups. Women were in the group A who were treated with misoprostol and women who were treated with oxytocin were in group B. Blood loss during delivery was estimated subjectively by the attending obstetrician.Results: A total number of 100 women were recruited for this study of which 50 women were in the group A and the rest of 50 women were in group B. In this study majority of the patients were belonged to age group 20 to 25 years in both the groups. In oxytocin group 2.0% have developed nausea, 4.0% patients have developed shivering. None have developed vomiting, diarrhoea, temperature. In misoprostol group 10.0% patients have developed nausea, 18.0% patients have developed shivering, 4.0% patients have developed rise of temperature, none have developed diarrhoea, vomiting. The differences were statistically significant. In this study 4.0% patients from oxytocin group and 2.0% patient from misoprostol group required blood transfusion.Conclusion: In conclusion less amount of blood loss is found in misoprostol group than oxytocin group.Journal of National Institute of Neurosciences Bangladesh, July 2021, Vol. 7, No. 2, pp. 152-155